1996
DOI: 10.1021/jp960568n
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Resonance Raman Spectroscopic Studies on the Radical Anions of Menaquinone and Naphthoquinone

Abstract: Quinones and their radical ion intermediates have been much studied by vibrational spectroscopy to understand their structure-function relationships in various biological processes. In this paper, we present a comprehensive analysis of vibrational spectra in the structure-sensitive region of both the naphthoquinone (NQ) and 2-methyl-1,4-naphthoquinone (MQ, menaquinone) radical anions using time-resolved resonance Raman and ab initio studies. Specific vibrational mode assignments have been made to all the vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…27 The aromatic C-C stretching modes are found to be at 1604 and 1579 cm 1 in NQ and at 1581 and 1604 cm 1 in 2-mNQ. 28 In the present case, the ring stretching modes are observed in the region 1620-1260 cm 1 (in both nRs and SERS). The nRs and SERS bands around 1390-1350 cm 1 are assigned to ring stretching mode of NQ coupled with CH 3 deformation mode of methyl group.…”
Section: Adsorption Of 2-mnq On Silver Surface Surface-enhanced Ramansupporting
confidence: 49%
See 1 more Smart Citation
“…27 The aromatic C-C stretching modes are found to be at 1604 and 1579 cm 1 in NQ and at 1581 and 1604 cm 1 in 2-mNQ. 28 In the present case, the ring stretching modes are observed in the region 1620-1260 cm 1 (in both nRs and SERS). The nRs and SERS bands around 1390-1350 cm 1 are assigned to ring stretching mode of NQ coupled with CH 3 deformation mode of methyl group.…”
Section: Adsorption Of 2-mnq On Silver Surface Surface-enhanced Ramansupporting
confidence: 49%
“…27 The Raman spectrum of NQ shows two wavenumbers at 1663 and 1678 cm 1 due to the C O stretching vibration. 26 Balakrishnan et al 28 observed asymmetric and symmetric C O stretching wavenumbers of NQ at 1681 and 1624 cm 1 , respectively, and in 2-mNQ at 1673 and 1669 cm 1 , respectively. 28 In the present case, nRs band at 1675 cm 1 and SERS bands at 1707 and 1671 cm 1 are assigned to the C O stretching vibration.…”
Section: Adsorption Of 2-mnq On Silver Surface Surface-enhanced Ramanmentioning
confidence: 99%
“…43 The pump beam is the third harmonic output of a 1064 nm fundamental from a Nd:YAG laser (DCR 11, Spectra Physics). The probe beam is obtained from an optical parametric oscillator (OPO) which is pumped by the third harmonic of 1064 nm output from an Nd:YAG laser (GCR 250, Spectra Physics).…”
Section: Methodsmentioning
confidence: 99%
“…18 In the case of 2-mNQ this mode appears around 1670 cm 1 . 8,22 The observed bands at 1634 (nRs) and 1646 cm 1 (SERS) in our spectra are assigned to C O stretching vibrations.…”
Section: Raman Spectral Studies 2-methyl-3-chloromethyl-14-naphthoqumentioning
confidence: 58%
“…The band at 1624 cm 1 is due to quinone C C stretching vibration and the band at 1599 cm 1 is assigned to aromatic C C stretching vibration. 22 The symmetric CH 3 deformation mode occurs around 1375 cm 1 , when the methyl group is next to an aromatic ring. 18 In the present case, the nRs band at 1338 cm 1 and the SERS band at 1369 cm 1 are due to the superposition of aromatic/quinone (C-C)/ (C C) stretching vibration of NQ and symmetric CH 3 deformation mode of a methyl group.…”
Section: Raman Spectral Studies 2-methyl-3-chloromethyl-14-naphthoqumentioning
confidence: 99%